PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DI MATAHARI DEPARTEMEN STORE KOTA PALU - Handayani, Andi Fitri; Hasanuddin, Bakri; Mahardiana, Lina (Katalogis, 2018)
The aim of the study is to analyze the influence of transformational leadership style on work satisfaction and Organizational Citizenship Behavior (OCB). The study was undertaken in Matahari Department Store in Palu with 163 samples. Data collection methods include interviews and questionnaires. Data analysis technique is Path Analysis. The result shows that transformational leadership has significant influence both on work satisfaction and OCB; transformational leadership has indirect influence on OCB while work satisfaction has significant influence on OCB.